2018
DOI: 10.1016/j.jallcom.2018.03.074
|View full text |Cite
|
Sign up to set email alerts
|

Effect of solidification rate on martensitic transformation behavior and adiabatic magnetocaloric effect of Ni50Mn35In15 ribbons

Abstract: Ni50Mn35In15 compound has become an archetype for investigating the functional properties of metamagnetic shape memory alloys. We have fabricated Ni50Mn35In15 melt spun ribbons to study the crystal structure, microstructure, martensitic transformation, magnetic properties and magnetocaloric effect as a function of the ribbon solidification rate controlled by the wheel speed. We have found that an increase of the cooling rate refines the alloy grain size, which, in turn, influences the chemical order of austeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…In this case, the slight reduction of │ΔTad│ in Fe8 can result from the aforementioned transition broadening and the heat transfer between matrix and secondary phase. It is worth mentioning that despite the reduction of ΔsT and │ΔTad│ in Fe8, a good agreement with literature values for "Fe-free" Ni-Mn-In of similar transition temperatures and field changes is obtained [47,[58][59][60].…”
Section: Transition Temperatures and Entropy Changessupporting
confidence: 87%
“…In this case, the slight reduction of │ΔTad│ in Fe8 can result from the aforementioned transition broadening and the heat transfer between matrix and secondary phase. It is worth mentioning that despite the reduction of ΔsT and │ΔTad│ in Fe8, a good agreement with literature values for "Fe-free" Ni-Mn-In of similar transition temperatures and field changes is obtained [47,[58][59][60].…”
Section: Transition Temperatures and Entropy Changessupporting
confidence: 87%
“…Another factor causing this difference is the microstructure change of the samples due to melt-spinning. It has been reported previously for Ni-Mn-In (Sn) ribbons that the value of T M→A decreases as the grain sizes decrease [28][29][30]. In melt-spinning, grain sizes can be controlled with wheel speed.…”
Section: Resultsmentioning
confidence: 95%
“…Crystal growth and compositional homogenization is enhanced after annealing of these rapidly quenched systems and, generally, increasing the structural and magnetic transition temperatures [55]. Aguilar-Ortiz et al [56] reported a shift of the martensitic transformation in Ni 50 Mn 35 In 15 ribbons from 300 to 285 K as the crystal size decreases from 7.3 to 0.9 µm. They also found variations in the Curie transition of both austenite and martensite (from 309 to 293 K and from 199 to 178 K, respectively).…”
Section: Other Factors Affecting Transition Temperaturementioning
confidence: 99%